Implied Term of Trust and Confidence: the Change in Approach of the Court of Appeal to the Requirement to Pay Redundancy Compensation - Nelson, Ross (Victoria University of Wellington Law Review, 2000)
This article examines the changing views of the Court of Appeal to payment of redundancy compensation where a contract of employment is silent. The author contrasts the leading cases, particularly Brighouse and Aoraki, and examines their differing approaches to issues such as the intention and interpretation of the Employment Contracts Act 1991, the extent of the implied term of mutual trust and confidence, and the perceived need for certainty in the law. The article concludes that the outcome is at least partly a result of changing judicial politics, and that perceptions of the correctness or otherwise of the current law will largely depend on readers views of ideology and politics.